High Apo B/Apo A-1 Serum Ratio As a Predictor of in-Hospital Major Adverse Cardiovascular Events in Acute Coronary Syndrome Patients - Diyantie Saputri; Hariadi Hariawan; Bambang Irawan (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2015)
Background: An increased level of apo B and decreased level of apo A-1 are thought to be better predictors of myocardial infarction than conventional lipid parameters in healthy individuals and/ or have coronary artery disease risk factors. Literatures said that HDL, LDL and apolipoprotein may have a role in haemostatic and thrombotic process. The present study aimed to investigate whether apo B/ apo A-1 ratio has a predictive role in hospitalised ACS patients to develop major adverse cardiac events (MACE). Methods: We performed a prospective cohort study and examined 182 ACS patients hospitalised in dr. Sardjito General Hospital Yogyakarta consecutively since September 2013, and evaluated ischaemia heart disease risk factors, measured concentration of apo B/apo A-1 ratio and conventional lipid parameters from plasma, and finally assessed the in-hospital MACE outcome. Apo B/Apo A-1 ratio cut off point in this study was taken from ROC curve analysis. Relation between in-hospital MACE with level of apo B/apo A-1 ratio was analysed using SPSS. Results: From 182 ACS subjects, 51 patients had MACE (MACE group) and 131 patients didn’t develop MACE (non-MACE group). From ROC curve, we set cut off point for apo B/apo A-1 ratio was 0,865. Subjects with an apo B/apo A-1 ratio ≥0,865 had a signifi cantly increased risk to suffer a cardiovascular event (MACE) during in-hospital follow-up. In a multiple logistic regression model, elevated apo B/apo A-1 ratio was an independent predictor for MACE during in-hospital follow-up (OR 3,17; 95%CI 1,299 - 7,738; p = 0,011). Conclusion: The results showed that the elevated apo B/apo A-1 ratio ≥0,865 was an independent predictor of MACE, with three-folds increase of risk compared to group of apo B/apo A-1 ratio < 0.865, during in-hospital follow-up in ACS patients.Keywords: apolipoprotein B; apolipoprotein A-1; apolipoprotein ratio; acute coronary syndrome; major adverse cardiovascular events